2017
DOI: 10.1051/matecconf/201710005032
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Development Necessarily Lead to Economic Growth? Evidence from China’s Cities, 2007–2014

Abstract: Abstract. Using data from 286 Chinese cities over the period [2007][2008][2009][2010][2011][2012][2013][2014], this paper investigates the impact of financial development on economic growth. Our results from traditional cross-sectional regressions, first-differenced GMM and system GMM regressions all show that financial development does not have any significant positive effects on economic growth, while some indicators of financial development show significant negative effects on growth. Our results are consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…On the other hand, private credit and government consumption are adversely correlated to GDP growth, as projected by theory. Negative interrelation of GDP growth and private credit is in line with previous findings by Zhao [2016], Halil Aric [2014 and Djalilov and Piesse [2011]. Government expenditures are not significant, but they are consistent with our theory and support prior researches in this area.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, private credit and government consumption are adversely correlated to GDP growth, as projected by theory. Negative interrelation of GDP growth and private credit is in line with previous findings by Zhao [2016], Halil Aric [2014 and Djalilov and Piesse [2011]. Government expenditures are not significant, but they are consistent with our theory and support prior researches in this area.…”
Section: Resultssupporting
confidence: 92%
“…The main reason of nonlinear impacts of financial development on economic growth could be too much finance in many countries, thus questioning the desirability of large financial sector (Benczur et al, 2019). Similarly, some researcher (for instance, Arcand et al, 2015;Cecchetti & Kharroubi, 2012;De Gregorio & Guidotti, 1995;Gennaioli et al, 2012;Zhao, 2017) found that excessive finance drags economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The study of [55] has supported the financial access help to promote saving channelize and growth using panel dataset covering 74 countries. [67] Study investigates the impact of financial development on economic growth at city level in China by using 286 Chinese cities over the period 2007-2014. The result of cross sectional regression suggested the negative impact on growth.…”
Section: Literature Reviewmentioning
confidence: 99%